2009
DOI: 10.1038/oby.2008.468
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Thermogenesis in Antipsychotic Drug‐induced Weight Gain

Abstract: The administration of antipsychotic drugs to human patients or experimental animals leads to significant weight gain, which is widely presumed to be driven by hyperphagia; however, the contribution from energy expenditure remains unclear. These studies aim to examine the contribution of shifts in energy expenditure, particularly those involving centrally mediated changes in thermogenesis, to the body weight gain associated with the administration of olanzapine to female Sprague Dawley rats. Olanzapine (6 mg/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
60
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 52 publications
15
60
0
3
Order By: Relevance
“…These results both confirmed that decreased energy expenditure and increased food intake/feeding efficiency contributed to increased weight gain induced by chronic olanzapine treatment [65,180].…”
Section: The Mechanisms Underlying Betahistine In Reducing Antipsychosupporting
confidence: 75%
See 1 more Smart Citation
“…These results both confirmed that decreased energy expenditure and increased food intake/feeding efficiency contributed to increased weight gain induced by chronic olanzapine treatment [65,180].…”
Section: The Mechanisms Underlying Betahistine In Reducing Antipsychosupporting
confidence: 75%
“…Additionally, it was also revealed that the expression of BAT UCP 1 and PGC-1α protein levels (biomarkers of thermogenesis) is reduced by chronic olanzapine treatment [65,180].…”
Section: The Mechanisms Underlying Betahistine In Reducing Antipsychomentioning
confidence: 99%
“…16,[47][48][49][50] Interestingly, the decrease in body temperature was followed by a much longer-lasting increase in temperature, which continued into the following light phase. Reactive hyperthermia was previously also reported after OLA was discontinued in rats that had been treated continuously for 18 days.…”
Section: Discussionmentioning
confidence: 99%
“…[96] Interestingly, a number of studies found that olanzapine (1-8mg/kg/day) causes dramatic increase of daily food intake particularly during short-term treatment (<2 weeks) in rats. [96][97][98][99] During long-term treatment, the olanzapine treatment group showed no significant difference in food intake from week 3-5, but maintained a higher body weight compared to the vehicle-treated control rats. [96][97]99] In addition, pair-fed rats which were given the same amount of food did not increase weight gain during short-term olanzapine treatment (6mg/kg/day, oral, 5days).…”
Section: Does Ampk-cpt1 Signaling Play a Different Role In The Three mentioning
confidence: 99%
“…[96][97][98][99] During long-term treatment, the olanzapine treatment group showed no significant difference in food intake from week 3-5, but maintained a higher body weight compared to the vehicle-treated control rats. [96][97]99] In addition, pair-fed rats which were given the same amount of food did not increase weight gain during short-term olanzapine treatment (6mg/kg/day, oral, 5days). [86] Patients treated with SGAs exert significantly decreased energy expenditure especially after chronic treatment (6-12 months).…”
Section: Does Ampk-cpt1 Signaling Play a Different Role In The Three mentioning
confidence: 99%